2010
DOI: 10.1159/000319946
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Brain-Derived Neurotrophic Factor Plasma Levels and Severity of the Illness, Recurrence and Symptoms in Depressed Patients

Abstract: Background: There is increasing evidence that the brain-derived neurotrophic factor (BDNF) is involved in the pathophysiology of mood disorders and that its peripheral levels represent a reliable mirror of its concentration in the brain. The aim of the present study was to measure BDNF plasma levels in patients affected by major depression and to explore the possible relationship between the biological parameter and characteristics of the illness. Method: BDNF plasma levels were evaluated in 30 inpatients suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 79 publications
2
38
2
1
Order By: Relevance
“…3B), which was clearly less pronounced compared to responders. In agreement with other findings using different antidepressive treatment approaches (Dell'Osso et al, 2010;Okamoto et al, 2008) we could show a significant correlation of HDRS-6 improvement with increased post-PSD serum BDNF levels at 8 am (t5) in all patients after 2 weeks (r p ¼ À0.612; p ¼ 0.0025) (Fig. 3C).…”
Section: Post-psd Bdnf and Therapy Response After 14 Dayssupporting
confidence: 92%
“…3B), which was clearly less pronounced compared to responders. In agreement with other findings using different antidepressive treatment approaches (Dell'Osso et al, 2010;Okamoto et al, 2008) we could show a significant correlation of HDRS-6 improvement with increased post-PSD serum BDNF levels at 8 am (t5) in all patients after 2 weeks (r p ¼ À0.612; p ¼ 0.0025) (Fig. 3C).…”
Section: Post-psd Bdnf and Therapy Response After 14 Dayssupporting
confidence: 92%
“…Further, no significant relationships were observed between any of the potential biomarkers and disease severity, based on HAM-D 17 or SDS scores. This finding is notable, given that such relationships have previously been reported in published studies of BDNF (Dell'Osso et al, 2010) and IL-6 (Bob et al, 2010), and a significant correlation between salivary cortisol levels and cognitive impairment in MDD patients has been observed (Hinkelmann et al, 2009). Not all analyses support definitive relationships between BDNF or IL-6 and depression, however (Gass and Hellweg, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…The neurotrophin BDNF plays a role in brain development and neuroplasticity, and has also been implicated in mediating treatment response in MDD (Castren and Rantamaki, 2010). Lower BDNF levels in patients with MDD compared with healthy controls have been reported (Bocchio-Chiavetto et al, 2010), and some studies, but not all (Jevtovic et al, 2011), have found an association between BDNF levels and severity of symptoms in untreated depressed patients (Dell'Osso et al, 2010). Levels of BDNF are reported to increase during treatment of depression (Hu et al, 2010;Matrisciano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, its functionality has not been assessed yet in depressed patients except in 2 negative studies performed in Asian patients [5,6], probably because there is no method to assess brain BDNF concentrations in vivo. Nonetheless, some data show that depressed patients have lower plasma BDNF levels than controls [7], suggesting that plasma BDNF may be a proxy of central BDNF in humans [8] and could be associated with the clinical characteristics of MDD [9]. Since the Met frequency of the Val66Met polymorphism is lower in Caucasian than in Asian individuals [10], and ethnicity may interfere with the impact of the Val66Met polymorphism in depressed patients [11], a different effect of the Val66Met polymorphism may exist in Caucasian as compared to Asian patients with MDD.…”
Section: Introductionmentioning
confidence: 99%